Emulation, Inequality, and Work Hours: Was Thorsten Veblen Right? - Samuel Bowles; Yongjin Park (University of Massachusetts, Department of Economics, 2004)
We investigate Veblen effects on work hours, namely the way that a desire to emulate the consumption standards of the rich induces longer work hours among the rest. Consistent with our model of these asymmetric social comparisons, greater inequality predicts longer work hours in ten OECD countries over the period 1963-1998. The country fixed effects estimates of the impact of inequality on hours are large, robust, and cannot be explained by conventional incentive effects. In the presence of Veblen effects, a social welfare optimum cannot be implemented by a flat tax on consumption but may be accomplished by progressive consumption taxes.
Keywords: H23; D31; D62; J22; 330; Interdependent utility; relative income; social comparisons; inequality; emulation; Veblen effects; work hours